Audit Quality and the Effectiveness of Accrual Reform: A Panel Study of Budget Composition Variance in Indonesia - Lestari, Putri Ayu; Fadilah, Resmi Afifah; Wahyuningsih (Summa : Journal of Accounting and Tax, 2024)
This study evaluates the impact of Indonesia’s 2015 accrual based accounting reform on budget composition credibility in subnational governments, utilizing the PI 2 Composition Variance indicator from the PEFA framework. The objective is to determine whether the adoption of accrual accounting improved alignment between planned and actual expenditures across economic classifications. The research applies a panel data methodology covering 514 Indonesian provinces and districts from 2011 to 2021. Using fixed effects regression models, the study incorporates a reform dummy, audit quality (measured by unqualified audit opinions or WTP), and various fiscal controls including PAD per capita, TKDD, personnel spending share, and PDRB. Robustness checks include alternative specifications and treatment of outliers and administrative splits. The results indicate that accrual reform is associated with a statistically significant reduction in budget composition variance. Furthermore, the reform’s impact is stronger in jurisdictions that received WTP audit opinions, underscoring the moderating role of audit quality. The findings suggest that institutional maturity, particularly audit capacity, amplifies the benefits of financial reporting reforms. In conclusion, accrual reform can improve fiscal discipline through enhanced compositional execution, especially when reinforced by high quality auditing institutions. These insights support policy efforts to integrate technical reforms with institutional strengthening. Future research should examine how these improvements influence service delivery and broader governance outcomes.